Strategic planning practices in the telecommunications industry: evidence from Saudi Arabia. Issue 4 (4th November 2019) - Alharbi, Mohammed; Dowling, Peter John; Bhatti, M. Ishaq
Abstract : Purpose: The purpose of this paper is to explore the current strategic planning practices in the MENA region by highlighting the practices in the Saudi telecommunications industry (Saudi TI) and the external and internal factors that influence strategic planning in the Saudi TI. Design/methodology/approach: The data comprised those from a questionnaire-based survey of a random sample of managers of Saudi TI firms, supplemented with data from secondary sources. Findings: The results revealed that most participating managers recognized the potential benefits of using strategic planning in their firms. Several significant factors that impacted on the decision-making process with regard to strategic planning in Saudi TI firms were identified. Originality/value: The main contribution of this paper is to fill an existing knowledge gap on strategic planning in a key industry such as the telecommunications industry in a country that is of importance as a business hub in the Middle East.